PENGGUNAAN ALIH KODE (CODE SWITCHING) DAN CAMPUR KODE (CODE MIXING) SEBAGAI STRATEGI DAYA TARIK IKLAN PADA MAJALAH GAYA HIDUP COSMOPOLITAN - M Rizky Kertanegara; Erwin Salpa Riansi (Jurnal Membaca Bahasa dan Sastra Indonesia, 2016)
Nowadays, the phenomenon of the use of English in advertising can be found in various media. The use of English in advertising can be found in tagline, headline or bodycopy. In language, the using and mixing of these two languages called code switching and code mixing. Lot of advertisers use these codes to persuade their specific and potential audiences on targeted marketing. Using content analysis method, this research wanted to see how big the use of code switching and code mixing on print media advertising that contained in Cosmopolitan Lifestyle Magazine. In addition, researchers also wanted to see how big the use of code switching and code mixing is elaborated with a rational approach to the attractiveness of advertising which consists of advertising features, competitive advantages, favorable price, news, and the popularity of appeal (Belch, 2001). The results shows the advertisements that use code switching and code mixing in Cosmopolitan lifestyle magazine more for its symbolic meaning and purpose as a rational strategy of the attraction of the product.